Topografia de controle de estímulos coerente em testes repetidos de pareamento ao modelo por identidade - BRINO, Ana Leda de Faria (2003)
In the context of matching-to-sample procedures with human subjects, after teaching some conditional relations, emergent performances, that are reflexive, symmetric, and transitive to directly taught relations, are often verified, fact that is not easily observed with nonhumans. These negative outcomes may be attributed to testing in extinction and consequent performance disruption. The objective of this study was to create testing conditions in extinction in order to overcome these problems. The subject was a capuchin monkey, which, as a result of his experimental history, could perform identity matchingto- sample (IDMTS) tests with reinforcement successfully. A zero delay IDMTS was used. Repeated tests of IDMTS and generalized IDMTS were arranged in a way that the test trials were interspersed with baseline ones. Tests with reinforcement were alternated with tests in extinction. These conditions were sufficient to maintain performance well above chance for the great most tests (20 out of 21). Capuchin monkey showed capacity to perform, succesfully, IDMTS with new stimuli with or without reinforcement.